Bacteriological profile, antibiotic susceptibility pattern and other factors related to neonatal meningitis: A cross-sectional hospital-based study from West Bengal - Barik, Kanai Lal; Biswas, Projesh; Das, Kuntal Kanti; Laha, Sumanta; Paul, Sudipto; Mondal, Saikat (Asian Journal of Medical Sciences, 2022)
Background: Neonatal sepsis and meningitis is an important cause of neonatal mortality and morbidity especially in the developing countries. Bacteriological profile of meningitis and antibiotic sensitivity pattern may vary from one region to another. Aims and Objectives: We have planned this study to know the etiological agent of neonatal meningitis with its antibiotic sensitivity profile and to evaluate some other associated risk factors of meningitis. Materials and Methods: This observational, cross-sectional study was done for a period of 1 year in the SNCU and NICU of a district Medical College of West Bengal in neonates presented with clinical sepsis and meningitis. Sepsis screen, blood culture, cerebrospinal fluid (CSF) study, and culture sensitivity was done and recorded along with demographic data, clinical presentation, outcome, and other associated factors. Results: We found meningitis in 55 neonates out of 250 clinical sepsis. CSF culture was positive in 42 cases with Escherichia coli (30.9%), Klebsiella (26.1%), Staphylococcus aureus (16.6%), Acinetobacter (14.2%) and Coagulase negative Staphylococcus (CoNS 11.9%) as prevalent organism. E. coli and Klebsiella were mostly sensitive to Amikacin, Levofloxacin, and Colistin whereas less sensitive to Cefotaxime, Pipercilin-tazobactam or Meropenem and Acinetobacter showed good sensitivity only to Levofloxacin. Among the gram-positive organism, S. aureus and CoNS were only sensitive to Linezolid, Vancomycin, and Teicoplanin. Conclusion: This type of study should help to make a proper antibiotic policy for an institution so that the empirical first-line antibiotic can be started with good effect in cases of neonatal sepsis and meningitis before the arrival of culture sensitivity report.